2007
DOI: 10.1590/s0004-282x2007000600023
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine-dependent epilepsy initially responsive to phenobarbital

Abstract: -Pyridoxine-dependent epilepsy is a rare autossomal recessive disorder characterized by recurrent seizures that are not controlled by anticonvulsant medications but remits after administration of pyridoxine. We report on a 30 day-old girl who presented with seizures during the first day of life, initially responsive to anticonvulsant therapy, which remitted within two weeks. Seizures were characterized as multifocal myoclonic jerks of upper and lower limbs associated with buccal-lingual oral movements and eyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Atypical cases have been reported, such as late-onset PDE starting after nineteen months of life, seizures that initially respond to antiepileptic medications and later become intractable. [3] Seizures that initially respond to very small doses of pyridoxine but later require larger doses, seizures during early life that do not respond to pyridoxine but controlled with pyridoxine several months later and prolonged seizure-free intervals that occur after pyridoxine discontinuation. The seizures are typically generalized tonic-clonic, although myoclonic seizures or infantile spasms have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical cases have been reported, such as late-onset PDE starting after nineteen months of life, seizures that initially respond to antiepileptic medications and later become intractable. [3] Seizures that initially respond to very small doses of pyridoxine but later require larger doses, seizures during early life that do not respond to pyridoxine but controlled with pyridoxine several months later and prolonged seizure-free intervals that occur after pyridoxine discontinuation. The seizures are typically generalized tonic-clonic, although myoclonic seizures or infantile spasms have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many reports of late presentation [10], and initial response to other AEDs [5], pyridoxine is still commonly considered only for the management of neonatal seizures by most physicians. Moreover, as previously reported, even that is quite uncommon in Indian patients [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pyridoxine dependency is often underdiagnosed, both because of occasional atypical presentation [2], and infrequent use of pyridoxine in intractable seizures of early onset in infants in India [3,4]. Moreover, occasional reports of initial response to phenobarbitone followed by later intractability [5], suggest that pyridoxine responsive seizures may not be identified in infancy. As this would likely lead to resistant/intractable seizure with or without developmental delay [1], we conducted this study to identify pyridoxine responsiveness in children with early-onset, idiopathic, intractable seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid remission of seizures, electrographic improvement, and developmental gains were noted after oral supplementation with 15 mg/kg per day pyridoxine at 5 months, after failure to respond to valproic acid or adrenocorticotropic hormone. In another report, a neonate with multifocal myoclonic seizures associated with tonic gaze deviation had an initial response to phenobarbital 5 mg/kg per day with seizure freedom between 10 and 15 days of age (Lin et al 2007). Relapse at age 1 month was associated with burst-suppression on EEG but a dramatic response to pyridoxine 50 mg daily starting approximately 12 hours after the first oral dose.…”
Section: Neonatal Metabolic Epilepsiesmentioning
confidence: 96%